2016
DOI: 10.1590/s1677-5538.ibju.2014.0291
|View full text |Cite
|
Sign up to set email alerts
|

Complete supine PCNL: ultrasound vs. fluoroscopic guided: a randomized clinical trial

Abstract: Introduction and Hypothesis:To compare complications and outcomes of complete supine percutaneous nephrolithotomy (csPCNL) with ultrasound guided and fluoroscopically guided procedure.Materials and Methods:In this randomized clinical trial study from January 2009 to September 2010, 26 of 51 patients with renal stones underwent csPCNL with ultrasonographic guidance in all steps of the procedure (group A), and the other 25 patients underwent standard fluoroscopically guided csPCNL (group B). All of the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
(46 reference statements)
4
21
1
1
Order By: Relevance
“…[ 15 ] A separate study has compared complications and outcomes of UGPN and FGPN using a complete supine position to perform the procedure. [ 16 ] It included 51 patients with renal stones who were randomly allocated such that 26 patients underwent UGPN, and 25 patients underwent the FGPN procedure. [ 16 ] The results of this study showed that both UGPN and FGPN demonstrated similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15 ] A separate study has compared complications and outcomes of UGPN and FGPN using a complete supine position to perform the procedure. [ 16 ] It included 51 patients with renal stones who were randomly allocated such that 26 patients underwent UGPN, and 25 patients underwent the FGPN procedure. [ 16 ] The results of this study showed that both UGPN and FGPN demonstrated similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] It included 51 patients with renal stones who were randomly allocated such that 26 patients underwent UGPN, and 25 patients underwent the FGPN procedure. [ 16 ] The results of this study showed that both UGPN and FGPN demonstrated similar outcomes. Moreover, ultrasonography could be a useful alternative to fluoroscopy during this surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to what we have reported in this case, several studies found no significant difference of complication between ultrasound-guided and fluoroscopy-guided PCNL. [16][17][18][19] Moreover, meta-analysis by Yang et al, even showed that ultrasound-guided PCNL had a significantly lower complication rate. 7 Our result and current evidence showed positive remarks of safety in performing X-rayfree ultrasound-guided PCNL.…”
Section: Discussionmentioning
confidence: 99%
“…Во многих публикациях предполагается неодинаковый уровень КЖ у больных после эктомии органа и его резекции [14][15][16][17][18][19][20][21]. Однако, как указывают B. Ljungberg и соавт., на данный момент только незначительное число исследований непосредственно посвящено сравнительной оценке КЖ пациентов, перенесших РНЭ или резекцию почки [22].…”
Section: Introductionunclassified